Analysis of the Impact of the COVID-19 Pandemic on Financial Performance in Various Industrial Sectors in Indonesia - Jacksen; Yantiana, Nella (LifeSciFi, 2025)
The COVID-19 pandemic significantly impacted the financial performance of companies across various industries in Indonesia, prompting an analysis of sectoral differences. This study aims to compare the financial performance of public companies in the mining, consumer goods, pharmaceutical, and agriculture sectors from 2019 to 2023. Using a quantitative approach, data from 40 companies, selected through purposive sampling based on large market capitalization and high trading liquidity, were analyzed. Financial performance was assessed using liquidity, debt-to-equity, return on assets, and total asset turnover ratios. A descriptive comparative method and the non-parametric Kruskal-Wallis test were employed to evaluate differences across sectors. The findings reveal significant differences in liquidity, profitability, and asset utilization efficiency, with the agriculture sector showing lower performance compared to others. The pharmaceutical sector demonstrated resilience in terms of profitability and asset efficiency, while the consumer goods and mining sectors maintained moderate stability. Debt-to-equity ratios remained uniform across sectors. These results highlight sector-specific financial dynamics during the pandemic, offering insights for investors, management, and policymakers. The study contributes to understanding financial resilience in emerging markets and suggests further research into subsector dynamics and additional financial metrics.